THE PRESERVATION OF RIVERBANK SETTLEMENT AS A TOURISM POTENTIAL IN THE CITY OF PALEMBANG, SOUTH SUMATERA - Maya Fitri Oktarini; Adiyanto Johannes; Listen Prima (Universitas Trisakti, 2021)
Aim: This study examines the current living culture of riverbank residents by observing the choice of factual house and the house preferences. A house is the physical characteristic of cultural products indicating the current living culture. The riverbank settlements are part of the historical development of the city of Palembang. Methodology and Results: This research focuses on the physical form of residential buildings from the perspective of socio-cultural preservation. Restoring the characteristics of the riverbank area is a necessary potential. The design process can be directed toward technical innovation, social aspect and the use of materials that correspond to the features of the area. Furthermore, the cultural ecological interaction has created a living culture in the riverbank. This is evident in the constructed houses of residents with structure, technology, and material conforming to the fluctuating conditions of the ecosystem. The settlement’s characteristics generate an image of a river city, which have also become a tourist attraction in Palembang. However, the living culture has changed due to the innovation in building technology, the shift in the focus of development, and the availability of natural resources which diminish these features. Conclusion, significance and impact of study: This will encourage tourists to visit the developed areas with a preservation approach, integrating new cultural living with the conservation of the river city features for tourism interest. Furthermore, the preservation of tourism activities are not only unchanged, but also an adaptation flexibility to continuously look for new forms for the symbiosis between man and nature.